(untitled) (Jurnal Intek Akuakultur, 2019)
The aim of this study to determined the exact dose of phytase enzymes to improve feed efficiency and growth of silver pompano. This research was held in February 2019 for 35 days at the Balai Perikanan Budidaya Laut (BPBL) Batam. The method was research experimental with a completely randomized design (CRD) with 4 treatments and 3 replications. Based on data analysis with One-Way ANOVA and Tukey phytase enzym give effect to silver pompano and the optimal result was on treatment D with the parameters nutrient efficiency utilization (24,69±1.36 %), weight specific growth rate (5,55±0.36 %), length specific growth rate (5,89±0.36 %).